Pola Interaksi Guru dan Orang Tua dalam Meningkatkan Keterampilan Motorik AUD Selama Masa Pandemi Covid 19 di TK Al Ikhlas - Nur Imam Mahdi; Misnan Misnan; Yulfina Roza; Erawati Br Ginting; Winda Lestari (Sekolah Tinggi Agama Islam Sumatera Medan, 2020)
This study aims to analyze: (1) various difficulties in learning courageously, (2) the pattern of cooperation between teachers and parents in improving children's motor skills, (3) relationships that increase cooperation in improving children's motor skills. The research method used is a qualitative research method, with a descriptive study approach. The results showed that the variety of learning difficulties during the Covid-19 pandemic, including because of the difficulty of the teacher in determining the type of motor-based learning activities for children, the difficulty of the teacher in compiling motor-based learning indicators, difficulty in assessing children's development, difficulty in assessing the honesty of children in carrying out activities motor learning. Both the conclusions of the second problem formulation related to the interaction patterns of teachers and parents in improving children's motor skills, there are two things that direct interaction and indirect interaction, while the less enthusiastic deposits of parents, different understanding between teachers and parents, internet networks not optimal, difficulties in implementing learning.